Evaluating an Image-Guided Operating Room with Cone Beam CT for Skull Base Surgery - Muhanna, Nidal; Douglas, Catriona M.; Daly, Michael J.; Chan, Harley H.L.; Weersink, Robert; Townson, Jason; Monteiro, Eric; Yu, Eugene; Weimer, Emilie; Kucharczyk, Walter; Jaffray, David A.; Irish, Jonathan C.; de Almeida, John R. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Importance Skull base surgery requires precise preoperative assessment and intraoperative management of the patient. Surgical navigation is routinely used for complex skull base cases; however, the image guidance is commonly based on preoperative scans alone.Objective The primary objective of this study was to assess the image quality of intraoperative cone-beam computed tomography (CBCT) within anatomical landmarks used in sinus and skull base surgery. The secondary objective was to assess the registration error of a surgical navigation system based on intraoperative CBCT.Design Present study is a retrospective case series of image quality after intraoperative cone beam CT.Setting The study was conducted at Toronto General Hospital and Princess Margaret Cancer Centre, University Health Network, Toronto.Participants A total of 46 intraoperative scans (34 patients, 21 skull base, 13 head and neck) were studied.Main Outcome and Measures Thirty anatomical landmarks (vascular, soft tissue, and bony) within the sinuses and anterior skull base were evaluated for general image quality characteristics: (1) bony detail visualization; (2) soft-tissue visualization; (3) vascular visualization; and (4) freedom from artifacts (e.g., metal). Levels of intravenous (IV) contrast enhancement were quantified in Hounsfield's units (HU). Standard paired-point registration between imaging and tracker coordinates was performed using 6 to 8 skin fiducial markers and the corresponding fiducial registration error (FRE) was measured.Results Median score for bony detail on CBCT was 5, remaining at 5 after administration of IV contrast. Median soft-tissue score was 2 for both pre- and postcontrast. Median vascular score was 1 precontrast and 3 postcontrast. Median score for artifacts on CBCT were 2 for both pre-and postcontrast, and metal objects were noted to be the most significant source of artifact. Intraoperative CBCT allowed preresection images and immediate postresection images to be available to the skull base surgeon. There was a significant improvement in mean (standard deviation [SD]) CT intensity in the left carotid artery postcontrast 334 HU (67 HU) (p < 10−10). The mean FRE was 1.8 mm (0.45 mm).Conclusion Intraoperative CBCT in complex skull base procedures provides high-resolution bony detail allowing immediate assessment of complex resections. The use of IV contrast with CBCT improves the visualization of vasculature. Image-guidance based on CBCT yields registration errors consistent with standard techniques.
Keywords: cone-beam CT; image-guided surgery; intraoperative imaging; head and neck cancer